Zebrafish Protocols for Neurobehavioral Research - Kalueff, Allan V.; Kalueff, Allan V.; Stewart, Adam Michael.; Stewart, Adam Michael. (Neuromethods, 2012)
Zebrafish (Danio rerio) play an integral role in biomedical research, enabling researchers to examine physiological mechanisms and pathways relevant to human pathogenesis and its therapy. That, along with their low cost, easy manipulation, short reproductive cycles, and physiological homology to humans, has made zebrafish a vital model organism for neuroscience research. Zebrafish Protocols for Neurobehavioral Research addresses protocols for both larval and adult models, written by the leading experts in the field of zebrafish research.  Part I of this book takes advantage of the high-throughput nature of larval models to offer protocols for research requiring high output, easily manipulated screens. The second half of the book focuses on the robust and sophisticated behaviors of adult zebrafish, suitable for the neurophenotyping of complex traits and multi-domain disorders.  Importantly, these models complement each other, working together to provide researchers with valuable insights into neurobiology of normal and pathological behavior. Thorough and cutting-edge, this volume is a useful, authoritative reference guide that should hold a coveted spot in zebrafish laboratories across the globe.